2021
DOI: 10.1126/sciadv.abf3885
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon regulates the stability of REV-ERBα to modulate hepatic glucose production in a model of lung cancer–associated cachexia

Abstract: Lung adenocarcinoma is associated with cachexia, which manifests as an inflammatory response that causes wasting of adipose tissue and skeletal muscle. We previously reported that lung tumor–bearing (TB) mice exhibit alterations in inflammatory and hormonal signaling that deregulate circadian pathways governing glucose and lipid metabolism in the liver. Here, we define the molecular mechanism of how de novo glucose production in the liver is enhanced in a model of lung adenocarcinoma. We found that elevation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…An alternate approach may be to assess the state of the circadian clock before and after MYC inhibition not in the tumor, but in a more easily accessed part of the body such as the blood. There is evidence from mouse models that primary tumors may distally disrupt circadian clocks throughout the body [ 173 , 174 ]. In human studies, patients with disrupted circadian activity, melatonin, or cortisol rhythms (all of which are distal processes to most tumors) had poorer prognosis across a wide variety of cancers [ 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Clinical Applications: Myc Inhibition and Measurement Of The Molecular Clock In Patientsmentioning
confidence: 99%
“…An alternate approach may be to assess the state of the circadian clock before and after MYC inhibition not in the tumor, but in a more easily accessed part of the body such as the blood. There is evidence from mouse models that primary tumors may distally disrupt circadian clocks throughout the body [ 173 , 174 ]. In human studies, patients with disrupted circadian activity, melatonin, or cortisol rhythms (all of which are distal processes to most tumors) had poorer prognosis across a wide variety of cancers [ 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Clinical Applications: Myc Inhibition and Measurement Of The Molecular Clock In Patientsmentioning
confidence: 99%
“…Furthermore, unlikely other disease-related malnutrition, cancer-related malnutrition, are thought to be different from those that lack nutrients in the absence of underlying diseases (i.e., hunger and anorexia nervosa). It has been observed that metabolic changes in cancer patients, such as inflammation, increased catabolic rate, and ineffective cyclic anabolic resistance, achieved through a tumor or cancer treatment may invite malnutrition in the patient ( 111 , 112 ). Apart from other clinical aspects in cancer-related malnutrition, the lack of adequate knowledge of nutritional intervention for cancer patients in caregivers is also a significant contribution in cancer-related malnutrition loss.…”
Section: Malnutrition and Cancermentioning
confidence: 99%
“…The circadian clock maintains cellular homeostasis and systemic physiology (31)(32)(33). However, altered circadian gene expression signatures are associated with several diseases including multiple cancer types (34)(35)(36)(37)(38)(39)(40)(41)(42). Human data from The Cancer Genome Atlas (TCGA) show a significant correlation between a subset of deregulated core clock genes and oncogenic driver pathways, survival rates, and tumor staging in 32 different cancer types (43).…”
Section: Introductionmentioning
confidence: 99%